Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Di Cafe Markas Ranjau (Studi Kasus Konsumen Cafe Markas Ranjau Mojosari) - Nurul, Lutvia; Setyaningsih, Eny; Utami, Budi (Philosophiamundi, 2024)
This research aims to analyze the factors that influence consumer purchasing decisions at Cafe Markas Ranjau Mojosari. In an era of intense business competition, especially in the culinary sector, understanding the factors that influence consumer decisions is crucial for business success. This research uses a quantitative approach with a survey method to collect data from cafe consumers. The results of the analysis show that product quality, service quality, company image and price have a significant influence on purchasing decisions. These findings provide important implications for the management of the Mine Headquarters Cafe in improving marketing and service strategies to attract more consumers and maintain loyal customers.